Long-Term Impact of Subclinical Hypothyroidism on Cardiovascular Outcomes in Adults: A Meta-Analysis of Cohort and Observational Studies - Wandala, Abali; Frimpong, Nana Akuoko-; Khan, Marium Nadeem; Mamdooh , Hussein Khalid; Alshaharli, Abdullah Ghaith; Mustafa, Sufyan; Akbar, Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Background: Subclinical hypothyroidism (SCH), defined by elevated thyroid-stimulating hormone (TSH) levels with normal free thyroxine (FT4), has been increasingly linked to cardiovascular disease. However, evidence remains mixed regarding its long-term impact on coronary outcomes. Objective: To evaluate the association between subclinical hypothyroidism and the risk of coronary heart disease (CHD) events, cardiovascular mortality, and all-cause mortality in adults using data from cohort and observational studies. Methods: A systematic search was conducted across PubMed, Scopus, Embase, and Web of Science from 2015 to 2024. Eligible studies included prospective cohorts reporting cardiovascular outcomes in adults with SCH versus euthyroid controls. Pooled hazard ratios (HRs) and relative risks (RRs) were calculated using a random-effects model. Subgroup analysis was conducted based on TSH levels (